EDUKASI KESEHATAN REPRODUKSI PADA KELOMPOK WANITA TANI DI DESA LANDASAN ULIN UTARA - Januarsih, Januarsih; Megawati, Megawati; Suhrawardi, Suhrawardi (JURNAL PENGABDIAN MANDIRI, 2025)
Women’s reproductive health is an important factor that affects the overall quality of life, both in physical, mental, and social aspects. However, limited understanding of reproductive health, especially in rural areas, is still a major problem. One example is Landasan Ulin Utara Village, where the majority of the population work as farmers. The farm women group in this village faces various challenges in maintaining reproductive health, especially related to reproductive hygiene issues, such as abnormal vaginal discharge. Lack of understanding on how to maintain reproductive hygiene and lack of access to health services affect women’s health in the village. The purpose of this community service activity is to provide education on reproductive health to a group of farm women in Landasan Ulin Utara Village. The approach used in this activity is a participatory community-based approach, with counselling methods, group discussions, and interactive question and answer sessions. Education focused on understanding reproductive hygiene, prevention of abnormal vaginal discharge, and the importance of accessing health services. In addition, this activity aims to reduce the existing social stigma related to the discussion of reproductive health issues. The results of this activity showed a significant increase in knowledge among participants. Before the education, the majority of participants did not know that abnormal vaginal discharge could be a sign of infection or a more serious health problem. After participating in the activity, more than 80% of participants were able to differentiate between normal and abnormal vaginal discharge and understood how to maintain reproductive hygiene. Through this activity, it is hoped that the women farmer groups in Landasan Ulin Utara Village will not only gain new knowledge, but also become agents of change who spread information about the importance of maintaining reproductive health in their communities.